Android-Based School Exam Information System for Sixth Grade Students at SD Negeri 23 Prabumulih - Myke Lastri Miyanti Myke; Andi Christian; Suhartini (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The school examination information system is a digital platform that aids in the administration of examinations for 6th-grade elementary school students. This research aims to develop an efficient and effective school examination information system to enhance the examination administration process at the elementary school level. The system development method waterfall and utilizes an object-oriented software design approach, considering the specific needs of elementary school examination administration. The developed system encompasses various features, such as examination scheduling, student data management, examination result recording, and provision of evaluation reports. The implementation of this system is expected to provide convenience for schools in managing and conducting school examinations, thereby facilitating smoother and more efficient learning processes.